2021
DOI: 10.1007/s41775-021-00120-x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the relationship between farm mechanization and labour requirement in India

Abstract: In many developing and emerging economies, better employment opportunities in the non-farm sector have increased rural wages due to labour shortages during the peak agricultural season. Increasing wages often cause a substitution of labour for mechanical power, but extensive use of labour-saving technologies may cause labour displacement and have serious equity concerns. Using the household and individual fixed effect estimation approach, this paper analyses the relationship between different types of farm mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Labor demand may then increase for not yet mechanized activities such as weeding and harvesting as farmers expand the area under cultivation or intensify and raise yields (Binswanger 1986;Pingali 2007). In India, Rajkhowa and Kubik (2021) found that the use of tractors and draft animals increased hired labor use by 12% due to area expansion and higher input use. Similar second-round effects have been observed in Botswana (Panin 1995) • Declining labor input, and rising unemployment: However, there are also cases where mechanization can lead to unemployment.…”
Section: Labor Productivity Labor Use and Employmentmentioning
confidence: 99%
“…Labor demand may then increase for not yet mechanized activities such as weeding and harvesting as farmers expand the area under cultivation or intensify and raise yields (Binswanger 1986;Pingali 2007). In India, Rajkhowa and Kubik (2021) found that the use of tractors and draft animals increased hired labor use by 12% due to area expansion and higher input use. Similar second-round effects have been observed in Botswana (Panin 1995) • Declining labor input, and rising unemployment: However, there are also cases where mechanization can lead to unemployment.…”
Section: Labor Productivity Labor Use and Employmentmentioning
confidence: 99%
“…In 1900, 41% of the US workforce was employed in agriculture, but in 2000, only 2% were employed in this primary sector [ 13 ]. This was due to the increasing mechanization of the sector, reaching mass production records [ 14 ]. In the EU, the dairy sector represents approximately 12% of the output coming from agriculture [ 15 ].…”
Section: The Current Worldwide Dairy Sectormentioning
confidence: 99%
“…Labour input may then increase for not yet mechanized activities such as weeding and harvesting as farmers expand the area under cultivation or intensify and raise yields (Binswanger, 1986;Pingali, 2007). In India, Rajkhowa and Kubik (2021) found that the use of tractors and draft animals increased hired labour use by 12 percent due to area expansion and higher input use. Similar second-round effects have been observed in Botswana (Panin, 1995), Ghana (Benin, 2015;Kirui, 2019;Cossar, 2019), Niger and Zimbabwe (Kirui, 2019), and Zambia (Adu-Baffour, Daum and Birner, 2019).…”
Section: Labour Productivity Labour Use and Employmentmentioning
confidence: 99%